2011
DOI: 10.1002/jgt.20528
|View full text |Cite
|
Sign up to set email alerts
|

Bipartite induced subgraphs and well-quasi-ordering

Abstract: We study bipartite graphs partially ordered by the induced subgraph relation. Our goal is to distinguish classes of bipartite graphs which are or are not well-quasi-ordered (wqo) by this relation. Answering an open question from [3], we prove that P 7 -free bipartite graphs are not wqo. On the other hand, we show that P 6 -free bipartite graphs are wqo. We also obtain some partial results on subclasses of bipartite graphs defined by forbidding more than one induced subgraph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 8 publications
0
35
0
Order By: Relevance
“…• (P 7 , Sun 1 )-free bipartite graphs. Well-quasi-orderability of this class was also shown in [10]. With no extra work this result can be extended to the labelled induced subgraph relation, because, as was shown in [10], every connected graph in this class is C 4 -free and (P 7 , C 4 )-free bipartite graphs contain no P 9 as a (not necessarily induced) subgraph.…”
Section: Subclasses Of Bipartite Graphsmentioning
confidence: 74%
See 2 more Smart Citations
“…• (P 7 , Sun 1 )-free bipartite graphs. Well-quasi-orderability of this class was also shown in [10]. With no extra work this result can be extended to the labelled induced subgraph relation, because, as was shown in [10], every connected graph in this class is C 4 -free and (P 7 , C 4 )-free bipartite graphs contain no P 9 as a (not necessarily induced) subgraph.…”
Section: Subclasses Of Bipartite Graphsmentioning
confidence: 74%
“…In [10], it was shown that graphs in this class are k-letter graphs. Therefore, they are well-quasi-ordered by the labelled induced subgraph relation.…”
Section: Subclasses Of Bipartite Graphsmentioning
confidence: 98%
See 1 more Smart Citation
“…Special classes, such as the set of bipartite graphs, have also been investigated under induced subgraph order. For example, it is conjectured in [19] that the P 7 -free bipartite graphs are not wqo under the induced subgraph relation; in [36] it is shown that this is indeed the case, but that the P 6 -free bipartite graphs are wqo. In [37], wqo classes of graphs defined by more than one induced subgraph obstruction are considered.…”
Section: Subgraph Ordermentioning
confidence: 99%
“…Similarly, a bit later Ding proved in [5] an analogous result for the subgraph relation. Other authors also considered this problem (see for instance [2,[11][12][13]). In this paper, we provide an answer to the same question for the induced minor relation, which we denote ≤ im .…”
Section: Introductionmentioning
confidence: 99%